Structural diversities and spectroscopic properties of bis and tris(1,10-phenanthroline)copper(II) complexes - Sujittra Youngme (2018)
The crystal structures of four new compounds containing bis and tris(1,10-phenanthroline)copper(II) complex units have been determined by X-ray crystallographic methods; [Cu(phen)3](S4O6)(S8) (1), [Cu(phen)3](BF4)2(2), [Cu(phen)2(OS2O7)] (3) and [Cu(phen)2(FBF3)](BF4) (4). The crystal structures of 1 and 2 are composed of discrete [Cu(phen)3]2+cations, (S4O6)2-and BF4-anions. The Cu(II) ion is octahedrally coordinated by the three phen ligands. As a consequence of the Jahn-Teller effect, the two axial Cu-N bonds are longer than the equatorial Cu-N bonds and the CuN6chromophores appear to be elongated rhombic octahedral with tetragonalities of 0.892 and 0.886 for 1 and 2, respectively. Complexes 3 and 4 consist of mononuclear units, the 5-coordinate Cu(II) environment being distorted square pyramidal (τ = 0.31) and distorted trigonal bipyramidal (τ = 0.66), respectively. The unidentate S2O82 -anion in 3 occupies the axial position, while the unidentate BF4-anion in 4 is coordinated in the trigonal plane. The crystal structures and their electronic properties including IR and EPR spectra are discussed and compared to other relevant complexes based on the Jahn-Teller effect. © 2006 Elsevier Ltd. All rights reserved.